2017
DOI: 10.1186/s40729-017-0103-5
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of three different methods of internal sinus lifting for elevation heights of 7 mm: an ex vivo study

Abstract: BackgroundVarious techniques are available for elevating the sinus membrane. The aim of this study is to evaluate three methods of indirect sinus floor elevation regarding elevation heights of 7 mm on the outcomes of membrane perforation, length of perforation, and time required to perform the procedure. MethodsThree different methods for indirect sinus lifting, bone added osteotome sinus floor elevation (BAOSFE), sinus floor elevation with an inflatable balloon, and crestal approach system (CAS kit) from OSST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
3
10
2
3
Order By: Relevance
“…This could be explained by the greater VEH permitted by the SCA versus osteotome approach. The positive results attributed to this kit demonstrated in this study are in concordance with the results observed in the ex vivo study of Yassin Alsabbagh et al, , where the SCA drill kit was shown to be superior to the osteotome technique in osteotomy preparation and breaking the sinus floor. These results were later corroborated in a clinical study by Kim et al, , who did not report any membrane perforations using the SCA drill kit, but reported an incident of acute maxillary sinusitis 5 months after surgery.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This could be explained by the greater VEH permitted by the SCA versus osteotome approach. The positive results attributed to this kit demonstrated in this study are in concordance with the results observed in the ex vivo study of Yassin Alsabbagh et al, , where the SCA drill kit was shown to be superior to the osteotome technique in osteotomy preparation and breaking the sinus floor. These results were later corroborated in a clinical study by Kim et al, , who did not report any membrane perforations using the SCA drill kit, but reported an incident of acute maxillary sinusitis 5 months after surgery.…”
Section: Discussionsupporting
confidence: 92%
“…The percentage of perforations found in the present study was 50%, higher than the data reported by Garbacea et al () and Nolan et al (), who reported a mean IoP rate of 40% and 41%, respectively. These rates were considerably less than the 58.4% reported by Yassin Alsabbagh et al (), or the 62.5% reported by Cho, Wallace, Froum, and Tarnow (). However, perforation during transcrestal sinus membrane elevation is not always detected, indirectly impacting postoperative complications and surgical outcome.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…These perforations are generally undetectable by the operator during the surgical procedure, thus eventually leading to further post‐surgical complications (Nolan, Freeman, & Kraut, ). Recently, other improved TSFE has been proposed; these include but are not limited to the balloon technique (Chan et al, ; Yassin Alsabbagh et al, ), the hydraulic elevation technique (Bensaha, ; Better et al, ; Tallarico, Better, De Riu, & Meloni, ), the piezotome technique and the reamer system (Yassin Alsabbagh et al, ). Among the TSFE techniques proposed, the reamer system (e.g., SCA‐Neobiotech, Seoul, South Korea) exhibits less trauma compared with other TSFE techniques (Gargallo‐Albiol, Tattan, Sinjab, Chan, & Wang, ; Kim, Lee, Park, Kim, & Oh, ; Yassin Alsabbagh et al, ).…”
Section: Introductionmentioning
confidence: 99%